INTERNET OF THING BASED CORN TEMPERATURE AND HUMIDITY CONTROL WITH FUZZY METHOD - kukuh winarso; Faikul Umam (Universitas Trunojoyo Madura, 2022)
Technological developments that are currently very helpful in work, one of which is in the agricultural sector. Farmers currently do not use technology, even though using technology can help farmers in completing their work. This study used the fuzzy logic method to control the temperature and humidity of corn. Several previous studies have focused more on making corn drying devices so they cannot remotely monitor temperature and humidity in corn. The aim of this research is to create an IoT-based corn temperature and humidity control system with the fuzzy logic method. This research focuses on making tools and systems that can monitor corn temperature and humidity remotely by utilizing a mobile application. The results of this study were two tests, the first experiment used corn with low or wet humidity and normal temperature while the second experiment used corn with high temperature and low humidity. The first experiment in the drying process showed a significant increase from the corn moisture value which was initially 400 to 649 in 15 minutes, while from 649 to 1003 it took 10 minutes. The second experiment took approximately the same time as the first experiment, which was about 15 minutes. When the humidity value has started to rise from 759 to 1005 it only takes approximately 10 minutes.